Assortative mating and Turkish marriage market - Mercan, Murat Anıl (Afyon Kocatepe Üniversitesi, 2012)
The degree of assortative mating shows the degree of similarity between couples. For instance, couples have similar age, weight, height or income. Economists usually investigate the income relationship. In addition, in marriage market the competition causes to have similar characteristics for spouses. Many papers try to calculate earnings correlations between husbands and wives. This paper tries to calculate the earnings correlations for Turkey and consider the effect of the sample selection. Our results show that there is a weak positive assortative mating in Turkey. It means that the correlation between couples' earnings is not high and the bias from the selection is small. Even though this result contradicts with the theoretical works, it is similar with empirical studies. In addition, we look at the assortative mating coefficients in different regions in Turkey. Mediterranean region has the biggest correlation coefficient whileBlack sea has a coefficient close to zero.

Gruplaşan eş seçiminin derecesi çiftler arasındaki benzerliklerin derecesini gösterir. Örneğin, çiftlerin yaşı, boyu, kilosu veya geliri benzeşmektedir. Ekonomistler ise daha çok gelir ilişkisini incelemektedir. Ayrıca, evlenme piyasasında eş seçimi için olan rekabet çiftlerin özelliklerinin birbirine benzemesine neden olmaktadır. Çeşitli makaleler karı koca arasındaki gelir korelasyonunu hesaplamaya çalışmıştır. Bu makale ise karı koca arasındaki gelir korelasyonunu Türkiye için hesaplarken örneklem seçimi sorununu da göz önüne almıştır. Sonuçlara göre Türkiye’de zayıf bir gruplaşan eş seçimi vardır yani çiftlerin gelirindeki korelasyon yüksek değildir ve örneklem seçimi sorunu da küçüktür. Bu teorik çalışmalarla çelişen bir sonuç olmasına rağmen ampirik çalışmalarla örtüşmektedir. Ayrıca, Türkiye’nin farklı bölgelerinde olan gruplaşan eş seçimi katsayıları da hesaplanmıştır. Akdeniz bölgesi en büyük korelasyon katsayısına sahipken Karadeniz bölgesi en küçüğe sahiptir.
Gruplaşan eş seçimi ve Türk evlilik piyasası
Keywords: Assortative Mating; Marriage; Earnings; Turkey